Historia y Derecho Homenaje a Carlos Ramos Núñez - Espinoza Coila, Michael (Facultad de Ciencias Jurídicas y Políticas - Universidad Nacional del Altiplano de Puno, 2022)
It is a work with investigations on the history of Law in homage to the jurist Carlos Ramos Núñez.